Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2003
DOI: 10.1105/tpc.012815
|View full text |Cite
|
Sign up to set email alerts
|

Control of Cellulose Synthase Complex Localization in Developing Xylem

Abstract: Cellulose synthesis in the developing xylem vessels of Arabidopsis requires three members of the cellulose synthase (CesA) gene family. In young vessels, these three proteins localize within the cell, whereas in older vessels, all three CesA proteins colocalize with bands of cortical microtubules that mark the sites of secondary cell wall deposition. In the absence of one subunit, however, the remaining two subunits are retained in the cell, demonstrating that all three CesA proteins are required to assemble a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

18
191
1
3

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 221 publications
(214 citation statements)
references
References 43 publications
18
191
1
3
Order By: Relevance
“…Since the scattering data showed no indications of oligomer forms beyond a trimer, we can conclude that this domain of ATCESA1 has determinants that contribute to lobe formation, but likely makes no direct contribution to the assembly of lobes into CSCs. Genetic and biochemical studies have shown that in Arabidopsis CESA1, -3, and -6 and CESA4, -7, and -8 isoforms are required for primary and secondary wall cellulose synthesis, respectively (Gardiner et al, 2003;Taylor et al, 2003;Persson et al, 2007). Other CESAs that play roles in tissue-specific processes are partially redundant with CESA6, as described in the introduction (Gardiner et al, 2003;Taylor et al, 2003;Somerville, 2006;Persson et al, 2007).…”
Section: Solution Structure Of Atcesa1catdmentioning
confidence: 99%
See 2 more Smart Citations
“…Since the scattering data showed no indications of oligomer forms beyond a trimer, we can conclude that this domain of ATCESA1 has determinants that contribute to lobe formation, but likely makes no direct contribution to the assembly of lobes into CSCs. Genetic and biochemical studies have shown that in Arabidopsis CESA1, -3, and -6 and CESA4, -7, and -8 isoforms are required for primary and secondary wall cellulose synthesis, respectively (Gardiner et al, 2003;Taylor et al, 2003;Persson et al, 2007). Other CESAs that play roles in tissue-specific processes are partially redundant with CESA6, as described in the introduction (Gardiner et al, 2003;Taylor et al, 2003;Somerville, 2006;Persson et al, 2007).…”
Section: Solution Structure Of Atcesa1catdmentioning
confidence: 99%
“…Genetic and biochemical studies have shown that in Arabidopsis CESA1, -3, and -6 and CESA4, -7, and -8 isoforms are required for primary and secondary wall cellulose synthesis, respectively (Gardiner et al, 2003;Taylor et al, 2003;Persson et al, 2007). Other CESAs that play roles in tissue-specific processes are partially redundant with CESA6, as described in the introduction (Gardiner et al, 2003;Taylor et al, 2003;Somerville, 2006;Persson et al, 2007). Furthermore, the stoichiometry of the CESA isoforms responsible for primary and secondary cell wall synthesis in Arabidopsis has recently been reported to be 1:1:1 (Gonneau et al, 2014; Hill et al, 2014).…”
Section: Solution Structure Of Atcesa1catdmentioning
confidence: 99%
See 1 more Smart Citation
“…A role for microtubules in aligning microfibrils is supported by a substantial body of evidence (Baskin, 2001;Burk and Ye, 2002;Gardiner et al, 2003). Nevertheless, some have argued that the parallelism between microtubules and microfibrils represents a correlated response to an unknown polarizing principle rather than a causal relation (Emons et al, 1992).…”
mentioning
confidence: 91%
“…A potent role for selfassembly is reasonable, given that cellulose microfibrils are well ordered even when assembled in vitro (Whitney et al, 1995). In some cells, self-assembly may suffice entirely, for example root hairs with helicoidal cell walls (Emons and Mulder, 1998); whereas in others, microtubule guidance may be paramount, for example in developing xylem, where parallel bands of a cellulose synthase subunit, observed as a green fluorescent protein-fusion, spread out immediately upon oryzalin treatment (Gardiner et al, 2003). However, most cells may lie between these extremes.…”
Section: Microtubule-microfibril Syndromementioning
confidence: 99%